PEMILIHAN ARSITEKTUR OPTIMAL MODEL NN DENGAN METODE KONTRIBUSI INCREMENT - Wuryandari, Triastuti (MATEMATIKA, 2006)
Neural Network is an information processing system that has certain characteristic in common with biological neural network. In development NN has been many applied in several surface, one of them is for forecasting. For the best application of NN, architecture has determined. One of methode to get optimal architecture NN is incremental contribution methods. This methods will to determine the size of hidden and input cell in the network with excluding respectively. One of the unit cell with a low incremental contribution will be exclution from network. The result shows that the incremental contribution methods is capable reducing the size of the network is propozed, so getting optimal architecture from network.